2019
DOI: 10.1021/acs.orglett.8b04090
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Electrochemical Nickel-Catalyzed Decarboxylative Sp2–Sp3 Cross-Coupling

Abstract: A one-pot electrochemical nickel-catalyzed decarboxylative sp2–sp3 cross-coupling reaction has been developed using redox-active esters prepared in situ from alkyl carboxylates and N-hydroxyphthalimide tetramethyluronium hexafluorophosphate (PITU). This undivided cell one-pot method enables C–C bond formation using inexpensive, benchtop-stable reagents with isolated yields up to 95% with good functional group tolerance, which includes nitrile, ketone, ester, alkene and selectivity over other aromatic halogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(54 citation statements)
references
References 25 publications
1
52
0
1
Order By: Relevance
“…Second, because two acids are used, the mode of activation can be swapped to improve yields with little extra synthetic effort (Scheme ): cyclopropane and adamantane carboxylic acids were best coupled as thioesters ( 25 , 33 ) and α‐amino acid NHP esters provided the best yields ( 13 – 15 ). This strategy is facilitated by the use of crude esters, formed from the corresponding uronium reagents, instead of purified materials (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, because two acids are used, the mode of activation can be swapped to improve yields with little extra synthetic effort (Scheme ): cyclopropane and adamantane carboxylic acids were best coupled as thioesters ( 25 , 33 ) and α‐amino acid NHP esters provided the best yields ( 13 – 15 ). This strategy is facilitated by the use of crude esters, formed from the corresponding uronium reagents, instead of purified materials (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…[12] Applying these optimized conditions to av ariety of different carboxylic acid pairs demonstrated that the chemistry was useful for the synthesis of dialkyl ketones and aryl alkyl ketones (Table 2). Functional group compatibility included acidic NÀHbonds (14,15,16,35), protected nitrogen atoms (6,13,23,32), and protected alcohols (37, 39). Notably, ap rimary alkyl bromide (9)d id not react with nickel or the nucleophiles present.…”
mentioning
confidence: 99%
“…Interestingly, the reaction of redox‐active ester 2 bd obtained from gabapentin, provided an unusual product which was thought to be generated by a 1,5‐hydrogen atom transfer (1,5‐HAT) prior to nickel mediated cross‐coupling (Figure a). As noted by others, the limitation of this procedure was the lack of reactivity towards tertiary redox‐active esters . Adamantane carboxylic acid and tert ‐butyl carboxylic acid phthalimide ester both failed to deliver desired product under our standard conditions.…”
Section: Figurementioning
confidence: 72%
“…11 Loren and coworkers reported an electroreductive decarboxylative coupling of carboxylate salts and aryl iodides, proceeding through in situ generation of NHP esters. 12 The photochemical and electrochemical methods reported to date all employ an excess of one of the electrophiles and form products that are either achiral or racemic -with the exception of the aforementioned auxiliary-based examples. Recognizing the benefits of electrochemistry, we sought to demonstrate that the enantioselective Nicatalyzed reductive alkenylation developed in our lab could be driven electrochemically.…”
Section: Anmentioning
confidence: 99%